Fluidic and Electronic Transport in Silicon Nanotube Biosensors. Issue 56 (10th May 2016) - Hibst, Nicolas; Steinbach, Annina M.; Strehle, Steffen
ABSTRACT: Silicon nanotubes (SiNTs) represent unique building blocks for future nanoscale biosensor devices merging electronic sensing and nanofluidics. Configured as ion-sensitive field effect transistors (ISFETs), SiNTs have great potential for charge sensing or label-free chemical detection in minute sample volumes flowing through their inner cavity. In the present study, doped SiNTs were synthesized from the gas phase in a bottom-up approach. To study their nanofluidic and electronic transport properties, single SiNTs were functionally integrated as ISFETs and coupled to a microfluidic system. The experimental results for ion diffusion through a SiNT are in full agreement with numerical calculations based on Fick's second law if a diffusion coefficient is assumed approximately one order of magnitude smaller than the bulk value.